A avaliatividade em pareceres de revista científica de linguística: uma perspectiva sistêmico-funcional - Cruz, Osilene Maria de Sá e Silva da (2012)
This study is part of GEALIN research group. It aims at analysing peer reviews from one Linguistics scientific journal and is based on the Systemic Functional Linguistics approach (HALLIDAY, 1994; HALLIDAY & MATTHIESSEN, 2004; EGGINS, 1994; THOMPSON, 1996; MARTIN, MATTHIESSEN & PAINTER, 1997), especially on the interpersonal metafunction, and Appraisal System (MARTIN & WHITE, 2005). The corpus consists of 67 peer reviews, organized in three groups: approved articles without restrictions (A), approved articles with restrictions (AR) and rejected articles (R). Using the paradigm of qualitative research approach, with methodological proceedings adapted from Martin & White (2005), the study identified thirteen topics (aboutness) discussed by referees: Abstract, Analysis, Argumentation, Bibliography, Contribution, Form, Language, Methodology, Objective, Result, Theme, Theory and Title. These topics were analysed under the perspective of Appraisal Subsystems: Attitude, Engagement and Graduation. Under Attitude, considerable occurrences of Appreciation were identified, with evaluations predominantly positive for group A and evaluations predominantly negative in groups AR and R. Instantiations of Engagement reveal a predominance of heteroglossia in all the three groups, although it was observed more instantiations of monoglossic positionings in group A. Group AR presents frequent occurrences of Dialogic Expansion through meanings of Entertain. Group R presents more frequency of Dialogic Contraction, predominantly through resources of Negation. Analysis related to Graduation reveals a predominance of Force, with more evidence to Intensification resources, demonstrating positive aspects in group A and negative significances in groups AR and R. Quantification instantiations were used more effectively in negative evaluations, indicating generalization in evaluation. This research can contribute to Appraisal studies and to the approach of scientific journals. It may also contribute to Journal RL1, providing information to improve its prestige